A time motion study in the immunization clinic of a tertiary care hospital of Kolkata, West Bengal - Amitabha Chattopadhyay; Ritu Ghosh; Sucharita Maji; Tapobroto Guha Ray; Saibendu Kumar Lahiri (Wolters Kluwer Medknow Publications, 2012)
Background: A time and motion study is used to determine the amount of time required for a specific activity, work function, or mechanical process. Few such studies have been reported in the outpatient department of institutions, and such studies based exclusively on immunization clinic of an institute is a rarity. Materials and Methods: This was an observational cross sectional study done in the immunization clinic of R.G. Kar Medical College, Kolkata, over a period of 1 month (September 2010). The study population included mother/caregivers attending the immunization clinics with their children. The total sample was 482. Pre-synchronized stopwatches were used to record service delivery time at the different activity points. Results: Median time was the same for both initial registration table and nutrition and health education table (120 seconds), but the vaccination and post vaccination advice table took the highest percentage of overall time (46.3%). Maximum time spent on the vaccination and post vaccination advice table was on Monday (538.1 s) and nutritional assessment and health assessment table took maximum time on Friday (217.1 s). Time taken in the first half of immunization session was more in most of the tables. Conclusion: The goal for achieving universal immunization against vaccine-preventable diseases requires multifaceted collated response from many stakeholders. Efficient functioning of immunization clinics is therefore required to achieve the prescribed goals. This study aims to initiate an effort to study the utilization of time at a certain health care unit with the invitation of much more in depth analysis in future.